2013
DOI: 10.3810/hp.2013.04.1020
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Canagliflozin Treatment in Older Subjects With Type 2 Diabetes Mellitus: A Randomized Trial

Abstract: Introduction:Canagliflozin is a sodium glucose co-transporter 2 inhibitor developed for the treatment of patients with type 2 diabetes mellitus (T2DM). Our randomized, double-blind, placebo-controlled, phase 3 study (www.clinicaltrials.gov: NCT01106651) evaluated the efficacy and safety of canagliflozin therapy in older subjects (aged 55-80 years) with T2DM inadequately controlled on their current regimen of blood glucose-lowering agents (any approved oral or injectable treatment). Methods: Subjects (N = 716) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

56
287
5
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 219 publications
(352 citation statements)
references
References 26 publications
56
287
5
4
Order By: Relevance
“…Reductions from baseline in alanine aminotransferase and serum urate were observed in the CANA groups compared with MET. Consistent with previous studies of CANA (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23), all CANA groups experienced early reductions in eGFR and commensurate increases in serum creatinine that attenuated over 26 weeks (Supplementary Fig. 3).…”
Section: Safety and Tolerabilitysupporting
confidence: 79%
See 3 more Smart Citations
“…Reductions from baseline in alanine aminotransferase and serum urate were observed in the CANA groups compared with MET. Consistent with previous studies of CANA (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23), all CANA groups experienced early reductions in eGFR and commensurate increases in serum creatinine that attenuated over 26 weeks (Supplementary Fig. 3).…”
Section: Safety and Tolerabilitysupporting
confidence: 79%
“…Smaller differences in HbA 1c were seen between treatment arms containing CANA100 and CANA300 in this study compared with previous studies where a dose response had been observed (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). However, HbA 1c lowering with CANA has been observed to be less dose-dependent as baseline HbA 1c increases (40).…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…6 The efficacy of canagliflozin in improving glycemic control, as measured by reductions in HbA1c and fasting and postprandial plasma glucose (FPG and PPG, respectively), and the overall safety and tolerability profile of canagliflozin in patients with T2DM have been reported previously. [7][8][9][10][11][12][13] Herein we report findings from a post hoc analysis of 1,5-AG levels using archived samples from a subset of patients who participated in a randomized, double-blind, placebocontrolled, Phase 3 study of canagliflozin monotherapy in patients with T2DM. 7 Detailed methods from the Phase 3 study of canagliflozin monotherapy have been reported elsewhere.…”
mentioning
confidence: 99%